KAJIAN SOSIOLOGIS GUGATAN KELOMPOK (CLASS ACTION) DALAM PERLINDUNGAN HUKUM KONSUMEN - Roni, Abdul (Faculty of Law, University of Palembang, 2021)
The perspective of Sociology of Law, the effectiveness of class action is an aspiration of the community which has been often ignored by producers. The main problem in law enforcement lies in the factors that may influence it. The legal factor itself, which is limited to the law only. Law enforcement factors are the parties that form and apply the law. Factors of facilities or facilities that support law enforcement. Community factors, namely as a result of work, creativity and taste based on human initiative in social life. Cultural factors, namely as a result of work, creativity and taste based on human initiative in social life. These factors affect law enforcement which is very influential for people who want to file class actions. Recognition theory and law enforcement factors in its application are very effective. Sociologically it must be implemented so that if there is a violation by the producer, the consumer can take a class action.